Analisis Kemampuan Literasi Sains di Sekolah Dasar Kota Medan - Mikael Pardomuan Hutabarat; Bonita Manullang; Anggreni Tamba; M. Surip (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the science literacy skills of students in primary schools in Medan City. The method used was a quantitative approach with a descriptive design. Data were collected through a science literacy test given to 31 students from 3 primary schools. The results showed that students' science literacy skills were still at a low level, with only 28% of students achieving an adequate level of literacy. The findings indicate the need for improvement in science teaching in primary schools to improve students' science literacy skills. This research is expected to provide insights for educators and policy makers in formulating more effective strategies to improve science literacy among primary school students.